Integration Impact of Electric Vehicles in Low-Inertia Power Networks - Louassef Mohamed Abd el Rahman; Belkhiri Mohamed Nadhir; ARIF Salem (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2024)
The integration of Renewable Energy Sources (RESs) in micro grid leads to a significant reduction in overall inertia, heightening susceptibility to instability. Fluctuations in load demand and RESs output exacerbate frequency instability. Additionally,the obstacle is the high cost of previous proposed solutions, which are batteries (ESS). posing further challenges to grid management. This thesis proposes an innovative control solution for the integration of Electric Vehicles (EVs) in low-inertia Microgrids (MGs) with high penetration levels of Renewable Energies (REs). The primary goal of the control approach is to enhance stability by combining Virtual Rotor Control (VRC) to provide the necessary inertia with Proportional Integral Derivative (PID) technique to alleviate the adverse effects of Phase-Locked Loop (PLL) measurement delay on the frequency response. Extensive simulations conducted within the MATLAB/Simulink environment demonstrate the critical role of EV integration in enhancing MG stability. The results show that deploying VRC significantly improves the frequency response, while including the PID controller yields substantial reductions in frequency deviations. The proposed control strategy exhibits remarkable resilience even under severe load variations and RE fluctuations. The optimization and validation of the control parameters further highlight the robustness and efficiency of the approach.
Electrical Power System